N6-Methyladenosine Methylation Analysis of Long Noncoding RNAs and mRNAs in IPEC-J2 Cells Treated With Clostridium perfringens beta2 Toxin - Yang, Jiaojiao; Yang, Qiaoli; Zhang, Juanli; Gao, Xiaoli; Luo, Ruirui; Xie, Kaihui; Wang, Wei; Li, Jie; Huang, Xiaoyu; Yan, Zunqiang; Wang, Pengfei; Gun, Shuangbao (Frontiers in Immunology, 2021)
Background: The n6-methyladenosine (m6A) modification is present widely in mRNAs and long non-coding RNAs (lncRNAs), and is related to the occurrence and development of certain diseases. However, the role of m6A methylation in Clostridium perfringens type C infectious diarrhea remains unclear. Methods: Here, we treated intestinal porcine jejunum epithelial cells (IPEC-J2 cells) with Clostridium perfringens beta2 (CPB2) toxin to construct an in vitro model of Clostridium perfringens type C (C. perfringens type C) infectious diarrhea, and then used methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) to identify the methylation profiles of mRNAs and lncRNAs in IPEC-J2 cells. Results: We identified 6,413 peaks, representing 5,825 m6A-modified mRNAs and 433 modified lncRNAs, of which 4,356 m6A modified mRNAs and 221 m6A modified lncRNAs were significantly differentially expressed between the control group and CPB2 group. The motif GGACU was enriched significantly in both the control group and the CPB2 group. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation analysis showed that the differentially methylated modified mRNAs were mainly enriched in Hippo signaling pathway and Wnt signaling pathway. In addition, the target genes of the differentially m6A modified lncRNAs were related to defense response to virus and immune response. For example, ENSSSCG00000042575, ENSSSCG00000048701 and ENSSSCG00000048785 might regulate the defense response to virus, immune and inflammatory response to resist the harmful effects of viruses on cells. Conclusion: In summary, this study established the m6A transcription profile of mRNAs and lncRNAs in IPEC-J2 cells treated by CPB2 toxin. Further analysis showed that m6A-modified RNAs were related to defense against viruses and immune response after CPB2 toxin treatment of the cells. Three m6A-modified lncRNAs, ENSSSCG00000042575, ENSSSCG00000048785 and ENSSSCG00000048701, were likely to play a key role in CPB2 toxin-treated IPEC-J2 cells. The results provide a theoretical basis for further research on the role of m6A modification in piglet diarrhea.